Kecanduan Internet dengan Fear Of Missing Out : Apakah Memiliki Keterikatan? - Beige, Eka Putri Marina; Matulessy, Andik; Suhadianto, Suhadianto (JIWA: Jurnal Psikologi Indonesia, 2023)
This study aims to determine the relationship between Fear Of Missing Out and Internet Addiction in college students. This research is a type of correlational quantitative research. The participants in this study were 350 students from 1490 student population of the Faculty of Psychology, University of 17 Agustus 1945 Surabaya, who were taken using incidental sampling. The data collection method was carried out by distributing questionnaires using the Google form using the internet addiction scale and the fear of missing out scale. This study uses non-parametric statistics using the Spearman's Rho correlation data analysis technique with a correlation score of 0.279 and a significance level of 0.000 (<0.05) which indicates that internet addiction and fear of missing out among students at the University of 17 Augustus 1945 Surabaya is quite high and has a strong relationship in the same direction. This means that if internet addiction among students is high, then the fear of missing out for these students is also high, and vice versa. Penelitian ini bertujuan untuk mengetahui hubungan antara Fear Of Missing Out dengan Kecanduan Internet pada mahasiswa. Penelitian ini merupakan jenis penelitian kuantitatif korelasional. Partisipan dalam penelitian ini sebanyak 350 mahasiswa dari 1490 populasi mahasiswa fakultas Psikologi Universitas 17 Agustus 1945 Surabaya diambil menggunakan insidental sampling. Metode pengumpulan data dilakukan melalui penyebaran kuesioner menggunakan google formulir dengan menggunakan skala kecanduan internet dan skala fear of missing out. Penelitian ini menggunakan statistik non parametrik dengan teknik analisis data korelasi Spearman's Rho dengan hasil skor korelasi 0,279 dan taraf signifikansi sebesar 0.000 (< 0.05) yang menunjukkan bahwa kecanduan internet dan fear of missing out pada mahasiswa Universitas 17 Agustus 1945 Surabaya cukup tinggi dan memiliki hubungan yang searah. Artinya jika jika kecanduan internet pada mahasiswa tinggi maka fear of missing out pada mahasiswa tersebut juga tinggi, begitu pula sebaliknya.